Distribution of Elemental Compositions of Muscovite Quarries in Turkey - KRİSTA, Eman; TURHAN, Şeref; KURNAZ, Aslı; HANÇERLİOĞULLARI, Aybaba (Politeknik Dergisi, 2022)
In this study, the contents of thirty-five elements (nine major-minor oxides, twenty-one heavy metals, and five other elements) in eighty-four muscovite samples collected from three commercially operated quarries in Manisa province of Turkey were determined using an energy dispersive X-ray fluorescence (EDXRF) spectrometer. The mean concentrations of SiO2, Al2O3, K2O, MgO, Na2O, Fe2O3, P2O5, TiO2 and CaO analyzed in mica samples were determined as 57.1, 32.8, 8.7, 2.9, 1.4, 0.8, 0.3, 0.3 and 0.3%, respectively. The mean concentrations of Cr, Zr, Mn, Zn, Ni, Co, Pb, Cu, Cd and Hg analyzed as primary toxic trace heavy metals in mica samples were found as 136.2, 124.6, 58.7, 19.2, 14.8, 6.8, 6.3, 2.6, 2.0 and 1.2 mg kg-1, respectively.
Keywords: Engineering; Mica; oxides; heavy metal; Hisarardı; EDXRF; Mühendislik; Mika; oksitler; ağır metal; Hisarardı; EDXRF; 13. Climate action; 6. Clean water